2022
DOI: 10.1038/s41598-022-10963-w
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and validation of sex-specific continuous metabolic syndrome scores for the Mexican adult population

Abstract: Traditionally the diagnosis of Metabolic syndrome (MetS) is binary (present/absent). The goal of this work is to propose a sex-specific continuous score to measure the severity of MetS in Mexican adults using waist circumference and body mass index as adiposity measures. MetSx-WC and MetSx-BMI indexes by sex were derived by confirmatory factor analysis (CFA) using data for 6567 adult participants of the National Health and Nutrition Survey 2018. The overall fit of the two proposed CFA models was excellent. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Developed models from studies in Iran, Korea, and the USA were approximately similar in terms of fit indices values 11 , 12 . Although the studies conducted in Mexico 14 and Singapore 13 showed higher fit indices, they were limited by not excluding participants with CVD as the MetS endpoint, and those on antihypertensive, antihyperlipidemic, and anti-diabetic medications as the important confounders. Moreover, the MetS severity score in the Mexican population was developed using the international diabetes federation (IDF) MetS definition, with assumption of MetS-WC (MetS-waist circumference) and not MetS as the latent variable, making it different in the design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Developed models from studies in Iran, Korea, and the USA were approximately similar in terms of fit indices values 11 , 12 . Although the studies conducted in Mexico 14 and Singapore 13 showed higher fit indices, they were limited by not excluding participants with CVD as the MetS endpoint, and those on antihypertensive, antihyperlipidemic, and anti-diabetic medications as the important confounders. Moreover, the MetS severity score in the Mexican population was developed using the international diabetes federation (IDF) MetS definition, with assumption of MetS-WC (MetS-waist circumference) and not MetS as the latent variable, making it different in the design.…”
Section: Discussionmentioning
confidence: 99%
“…With the use of confirmatory factor analysis (CFA), Gurka et al 11 took a step further by considering the correlation of these components as an indicator of the underlying processes involved in MetS, as well as the variation of this correlation by sex (male/female) and race (Hispanic, Non-Hispanic Black, and Non-Hispanic White). MetS severity scores were previously developed using CFA in the American (White, Hispanic, Black races), Korean, Mexican, and Singaporean adults 11 14 . However, no MetS severity score has been created for the adult population in Western Asia.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some studies have suggested that TyG is a better indicator than VAI also in adults. [ 32 , 46 ]. Nevertheless, it should be taken into account that in studies that indicate that VAI or Tyg is a superior predictor, the male/female ratio of participants may have affected the results.…”
Section: Discussionmentioning
confidence: 99%